Энергетический кризис разрешит альтернативная энергетика - Березуцкий, Вячеслав Владимирович; Березуцкая, Н. Л. (НТУ "ХПИ", 2014)
Рассмотрены традиционные источники получения энергии и показаны их недостатки. Выполнены исследования по определению наличия энергии в пирамидках, построенных по принципу египетских пирамид. Полученные результаты позволили сделать вывод о перспективности разработки технологий получения энергии в пирамидах.

Considered traditional sources of energy and show their weaknesses. Studies were performed to identify the presence of energy in the pyramids that are built at the principle of the Egyptian pyramids. The results obtained led to the conclusion about the forecasts of the development of energy technologies in the pyramids.
Energy crisis will be allowed alternative energy
Keywords: источники энергии; недостатки; преимущества; энергия космоса; пирамиды; energy; energy sources; disadvantages; advantages